Mouse adipose tissue stromal cells give rise to skeletal and cardiomyogenic cell sub-populations - Dromard, Cécile; Barreau, Corinne; André, Mireille; Berger-Müller, Sandra; Casteilla, Louis; Planat-Benard, Valerie (Frontiers in Cell and Developmental Biology, 2014)
We previously reported that adipose tissue could generate cardiomyocyte-like cells from crude stromal vascular fraction (SVF) in vitro that improved cardiac function in a myocardial infarction context. However, it is not clear whether these adipose-derived cardiomyogenic cells (AD-CMG) constitute a homogenous population and if AD-CMG progenitors could be isolated as a pure population from the SVF of adipose tissue. This study aims to characterize the different cell types that constitute myogenic clusters and identify the earliest AD-CMG progenitors in vitro for establishing a complete phenotype and use it to sort AD-CMG progenitors from crude SVF. Here, we report cell heterogeneity among adipose-derived clusters during their course of maturation and highlighted sub-populations that exhibit original mixed cardiac/skeletal muscle phenotypes with a progressive loss of cardiac phenotype with time in liquid culture conditions. Moreover, we completed the phenotype of AD-CMG progenitors but we failed to sort them from the stromal vascular fraction. We demonstrated that micro-environment is required for the maturation of myogenic phenotype by co-culture experiments. These findings bring complementary data on AD-CMG and suggest that their emergence results from in vitro events.